COVID-19 and thrombosis - Verma, Kavita; Sharma, Anjali; Bulsara, Shahzad Sarosh (International Journal Of Community Medicine And Public Health, 2021)
The first case of novel corona virus disease (COVID-19) was reported in China and undoubtedly today this disease has rapidly crossed borders, infecting people throughout the world. There are heaps of complications related to COVID-19 namely acute respiratory failure, acute liver and kidney injury, bacterial and fungal infections, and septic shock. Vascular thrombosis is another burden that COVID-19 is pilling on to the load of its complications. Venous thromboembolism namely deep vein thrombosis and pulmonary thromboembolism; pulmonary microvasculature thrombosis and systemic arterial thromboembolic events like limb ischemia, myocardial ischemia/infarction and cerebrovascular thrombosis are being increasingly reported in COVID-19 patients.